The The Effectiveness of TPSS Method in Teaching Reading Comprehension at SMP Tahfidz Asy-Syadzili Putukrejo Gondanglegi Malang: English - Kharunia Imatul Umah Nia; Tyas Alhim Mubarok; Istina Atul Makrifah (Prodi Tadris Bahasa Inggris, 2023)
In order to learn and teach effectively, students need to have a comprehensive knowledge of the English language and understand its meaning. Students must be able to understand the language both orally and in writing if they have mastery of vocabulary. The purpose of this study is to apply TPSS in learning reading comprehension at Tahfidz Asy - Syadzili Middle School. It is hoped that learning by using the TPSS method, students will become more motivated to learn and understand English reading well. Teachers obtain learning methods that can be used for learning reading comprehension so that learning is not too monotonous and not just the teacher's knowledge. The method used in this research is a quantitative method with a quiz-experimental approach that uses the population in this study is 7 grades of SMP Tahfidz Asy – Syadzili totaling 40 students. Research results In the application of the TPSS method by the teacher, this strategy has been going well and the teacher has carried out all the stages. The TPSS method can assist teachers in conveying quite a lot of understanding of the material well. This can be seen from the teacher's observation sheet which states that 100% of the stages were carried out in the first and second meetings, while the three stages were carried out by 98%, 12% were not implemented. This strategy was used by the teacher to guide students to become independent learners in accordance with the learning objectives. So that the quality of teacher guidance to students can also increase.